Classification of knives Russia in the theory and practice of historical fencing (for example, spears) - Бугорська [Olga Bugorskaya] Ольга Анріївна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Based on the study and analysis of literary sources, a classification of weapons that have similar geometric parameters with a spear. Physical models made spears and weapons similar to it with respect to geometric and functional parameters, and experimentally compared functionality different types of weapons and spears when the slashing attacks on protective gear VII-XIV centuries. Based on these results was the correction classification of knives Russia. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>